Effect of live sperm count per inseminate on pregnancy rate in buffaloes - PRABHAKAR, J H; KALSI, J S; JANI, V R; PATEL, S H (The Indian Journal of Animal Reproduction, 2023)
Semen from 1 0 MUITah buffalo bulls was split-frozen in 0.5 ml French straws to get mean concentrationsof22.6, 17.3, l l.0and 8.Sx 106(Cl, C2, C3 & C4, respectively)spermatozoa per dose. A total of1941 buffaloes wereinseminated at 20 AI centres and pregnancy rates were 59.4, 58.1, 66.7 and 52.4 per cent for CI, C2, C3 and C4respectively. Pregnancy rates differed significantly among bulls and among technicians. After correcting for thevariations due to bulls as well as technicians, the pregnancy rates were not affected by the sperm concentrationemployed. It is concluded that the reduced sperm concentration up to 11 x l 06 spermatozoa or even lowerconcentration (8.5 million) per inseminate does not affect the overall fertility of buffalo bull semen, though individualdifferences exist between bulls regarding maintenance of fertility at lower sperm concentration per inseminate.
Keywords: Buffalo bull; Number of spermatozoa; Pregnancy rate.